Mario Trinchero e Leonardo Mosso Un incontro tra filosofia e architettura (Materiali di Estetica. Terza serie, 2021)
During their lifetime, Mario Trinchero, philosopher, and Leonardo Mosso, architect and artist, cultivated a constant dialogue between philosophical and architectural thought. We publish here an unpublished Trinchero’s essay concerning his friend Mosso’s idea of architecture. Trinchero aims to identify the zero-language of Mossian architecture as an ideography that is determined in architectural matter.
Keywords: Philosophy; Language of Architecture; Experimental Ideography